Corporate investment and growth opportunities: The role of R&D-capital complementarity - Sanford, Anthony; Yang, Mu-Jeung (Journal of Corporate Finance, 2022)
How does the interaction of uncertainty and R&D impact corporate investment? We provide evidence that R&D significantly increases corporate investment responsiveness to PVGO news and uncertainty shocks. These results are consistent with predictions from the R&D-based real options model of corporate investment. To establish credible causal results we combine new measures of systematic and firm-specific PVGO shocks, for which we utilize stock price and option data, with exogenous measures of R&D capital stocks derived from panel variation in state R&D tax credits. We also rule out a number of potentially competing explanations for our results, including firm-level differences in lumpiness of investments, financial frictions, lifecycle growth opportunities or moral hazard-implied asset substitution or risk shifting.